Healed Lesions of Human Cutaneous Leishmaniasis Caused By Leishmania major Do Not Shelter Persistent Residual Parasites - Sghaier, Rabiaa M.; Benhnini, Fouad; Guerfali, Fatma Z.; Attia, Hanène; Bali, Aymen; Zaatour, Amor; Mkannez, Ghada; Gharbi, Adel; Belhaj-Hamida, Nabil; Dridi, Hichem; Ben-Salah, Afif; Dellagi, Koussay; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
• In human cutaneous leishmaniasis (HCL) caused by Leishmania (L.) major, lesions heal spontaneously and induce a Th1-immunity that confers solid protection against reinfection. The same holds true for experimental leishmaniasis in C57BL/6 mice. However residual L. major parasites persist after animal cure, inducing sustainable memory immune responses and resistance to reinfection. Whether parasites also persist in scars of cured HCL caused by L. major is still unknown and has not been investigated thus far, although described in HCL caused by other Leishmania species. Cutaneous scars from 53 volunteers with healed HCL caused by L. major were biopsied and analyzed for residual parasites by i) microscope detection of amastigotes, ii) culture on biphasic medium, iii) inoculation to the footpad of highly susceptible inbred BALB/c mice, and iv) amplification of parasite kDNA by a highly-sensitive RT-PCR. Results show that scars of healed lesions of HCL caused by L. major do not contain persistent parasites, suggesting that this form likely induces a sterile cure at least within scars. This contrasts with other Leishmania species causing chronic, diffuse, or recidivating forms of leishmaniasis were parasites can persist in healed lesions. The possibility of long-term immunity sustained and boosted by alternative mechanisms should be taken into consideration in vaccine development toward L. major infection.